Spatial Structure of Marine Host-Associated Microbiomes: Effect of Taxonomy, Species Traits, and Study Design - Schellenberg, Lisa; Clarke, Laurence J. (Frontiers in Marine Science, 2020)
Marine host-associated microbiomes have a strong influence on their host’s function and are shaped by selection, dispersal, diversification, and drift. These processes can lead to spatially structured microbiomes, with potential implications for host fitness in different locations. We review the literature on marine host-associated microbiomes to identify if spatially structured microbiomes are more prevalent in certain taxonomic groups, are linked to species traits, or sampling design and methodology. The 28 papers analyzed represented 38 host species, with spatial structure detected in 74% of species, increasing to 81% when restricted to studies using high-throughput DNA sequencing. Spatial structure was detected in all coral and marine mammal microbiomes, but was less common in fish (63%) and sponges (46%). Mobile species and external tissues were more likely to show spatially structured microbiomes than sessile species and internal tissues. We found no relationship between spatial structuring and maximum distance between sampling sites, with studies on large (>1000 km) and small spatial scales (<100 km) almost as likely to show spatial structure (87% vs. 73%). Our results support using high-throughput sequencing for studying marine host-associated microbiomes due to better taxonomic resolution compared to other methods. Given the observed generality of spatially structured microbiomes, future studies should test whether microbiome variation between locations effects host fitness. Researchers should include sufficient environmental microbiome sampling and host data to distinguish host and environmental effects. This will help resolve the relative importance of selection, dispersal, diversification and drift in shaping marine host-associated microbiomes.